Primary renal Ewing sarcoma in a postpartum female: a case report - Feng, Xiaohui; Wang, Xiaomei; Gao, Feng (Frontiers in Oncology, 2025)
Primary renal Ewing sarcoma (rES) is an extremely rare and aggressive malignancy in adults with nonspecific clinical and imaging features. The diagnosis of rES during pregnancy is particularly uncommon. Here, we report a unique case of rES in a 35-year-old postpartum female who presented with lumbar pain and hematuria. Histopathological and immunohistochemical analyses confirmed the diagnosis of rES. This case highlights the importance of considering rES in young females with renal masses, particularly during the postpartum period.